The effect of mindfulness-based group skill training for mothers who have children with intellectual disabilities during the COVID-19 pandemic: A feasibility study - ÜNSAL, GÜL (My University, 2024)
Objectives: This study aimed to assess the effects of mindfulness-based skill training on stress, cognitive emotion regulation (CER), and mindfulness levels in these mothers. Methods: The study was conducted in Türkiye and is a single-arm, mixed-method feasibility study. Thirty-one mothers were given a 6-week online mindfulness-based group skill training. Although the study started with 43 mothers, it was completed with 31 mothers due to drop-outs (5) and a lack of follow-up (7) measurements and analyses were made. Perceived stress scale (PSS), mindfulness attention awareness scale and CER scale were used in the study. Results: The study had a strong recruitment rate of 71.66%. A statistically significant difference was found in the PSS scores of the participants at the pretest and post-test. There was no statistically significant difference between baseline and follow-ups in the Mindful attention awareness scale score and CER questionnaire score. Conclusion: It can be noted that the mindfulness-based skill training program given online during the COVID-19 period is effective in reducing the stress levels of mothers of children with intellectual disabilities. Keywords: COVID-19; intellectual disability; mindfulness; mother; stress.
Keywords: Tıp; Hemşirelik; Sağlık Bilimleri; Medicine; Nursing; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Psikiyatri; Clinical Medicine (Med); Clinical Medicine; Psychiatry; Psikiyatrik Ruh Sağlığı; Psikiyatri ve Ruh Sağlığı; İleri ve Uzman Hemşirelik; Psychiatric Mental Health; Psychiatry and Mental Health; Advanced and Specialized Nursing; COVID-19; intellectual disability; mindfulness; mother; stress